The Role of Calcium/Calcium-Dependent Protein Kinases Signal Pathway in Pollen Tube Growth - Yang, Hao; You, Chen; Yang, Shaoyu; Zhang, Yuping; Yang, Fan; Li, Xue; Chen, Ning; Luo, Yanmin; Hu, Xiuli (Frontiers in Plant Science, 2021)
Pollen tube growth as a key step for successful fertilization is essential for angiosperm survival and especially vital for the grain yield in cereals. The process of pollen tube (PT) growth is regulated by many complex and delicate signaling pathways. Among them, the calcium/calcium-dependent protein kinases (Ca2+/CPKs) signal pathway has become one research focus due to which Ca2+ is a well-known essential signal molecule for PT growth, which can be instantly sensed and transduced by CPKs to control myriad biological processes. In this review, we summarize the recent progress in understanding the Ca2+/CPKs signal pathway governing PT growth and also discuss the question of how this pathway regulates PT growth.